The two-receptor model of lipoprotein clearance: tests of the hypothesis in "knockout" mice lacking the low density lipoprotein receptor, apolipoprotein E, or both proteins. - Ishibashi, S (1994)
Apolipoprotein E (apoE) is hypothesized to mediate lipoprotein clearance by binding to two receptors: (i) the low density lipoprotein receptor (LDLR) and (ii) a chylomicron remnant receptor. To test this hypothesis, we have compared plasma lipoproteins in mice that are homozygous for targeted disruptions of the genes for apoE [apoE(-/-)], the LDLR [LDLR(-/-)], and both molecules [poE(-/-); LDLR(-/-)]. On a normal chow diet, apoE(-/-) mice had higher mean plasma cholesterol levels than LDLR(-/-) mice (579 vs. 268 mg/dl). Cholesterol levels in the apoE(-/-); LDLR(-/-) mice were not significantly different from those in the apoE(-/-) mice. LDLR(-/-) mice had a relatively isolated elevation in plasma LDL, whereas apoE(-/-) mice had a marked increase in larger lipoproteins corresponding to very low density lipoproteins and chylomicron remnants. The lipoprotein pattern in apoE(-/-); LDLR(-/-) mice resembled that of apoE(-/-) mice. The LDLR(-/-) mice had a marked elevation in apoB-100 and a modest increase in apoB-48. In contrast, the apoE(-/-) mice had a marked elevation in apoB-48 but not in apoB-100. The LDLR(-/-); apoE(-/-) double homozygotes had marked elevations of both apolipoproteins. The observation that apoB-48 increases more dramatically with apoE deficiency than with LDLR deficiency supports the notion that apoE binds to a second receptor in addition to the LDLR. This conclusion is also supported by the observation that superimposition of a LDLR deficiency onto an apoE deficiency [apoE(-/-); LDLR(-/-) double homozygotes] does not increase hypercholesterolemia beyond the level observed with apoE deficiency alone.